Multiple paternity and competition in sympatric congeneric reef fishes, Embiotoca jacksoni and E. lateralis - CÉLINE M. O. REISSER; RICARDO BELDADE; GIACOMO BERNARDI (Molecular Ecology, 2009)
The black surfperch Embiotoca jacksoni and the striped surfperch E. lateralis (Embiotocidae, Perciformes) are livebearing temperate reef fishes that live sympatrically over a large portion of their distribution range, where they exhibit strong ecological competition. In order to assess whether mating strategies reflect competition, we investigated multiple paternity in these two species in an area of sympatry. We sampled 24 pregnant females (12 for each species) in Monterey Bay, California, used microsatellite analysis and assessed paternity with the COLONY software. While broods are relatively small (12 to 36 offspring), they were always sired by multiple fathers (2 to 9), with no correlation between the size of a brood and the number of fathers. The number of sires for each brood was not significantly different between the two species (approximately 3.5 sires per brood). We tested the deviation from stochasticity of fathered offspring for each father in one brood. Results showed a significant deviation for both E. jacksoni and E. lateralis . However, this deviation was not found to be significant between species. The striking similarity in the dynamics of multiple paternity in these species, when sampled in sympatry, may result from several alternative scenarios, including phylogenetic inertia, reproductive behaviour, and ecological competition.